Fashion education sustainability practices among fashion design students in vocational colleges - Sarimah binti Abu Bedor; Arasinah Kamis; Farah Najwa binti Ahmad Puad (Jurnal Pendidikan Vokasi, 2024)
The practice of sustainability in fashion education is practised by students related to environmental issues through a curriculum approach, independent activities, pedagogy, teaching & and learning strategies and external collaboration in preparation for facing the real world of the fashion industry. However, observations show that material waste and imprudent material management occur during the task development process, contributing to environmental pollution. Thus, this study aims to identify the level of sustainability practices in fashion education among students of Fashion Design at Vocational Colleges. The theories and models used in this study are Norm Activation Theory, environmentally sustainable textile and apparel consumption Model (ESTA- Environmentally sustainable textile and apparel consumption), Model of Predictors of Environmentally Responsible Behaviour (Model of Predictors of Environmental Behaviour: PEB) and Behavioural Change System Model (Behavioural change system: KAP). The design of this study uses a quantitative cross-sectional survey strategy of 330 students using stratified random sampling and purposive random sampling techniques. A Likert scale (5-point) questionnaire instrument adapted and modified from previous studies was used to obtain data. IBM SPSS version 26.0 software was used as a descriptive analysis tool by looking at the mean value and standard deviation. Findings of the sustainability practices in fashion education among fashion design students at vocational colleges show a high level (M=3.88, SD=0.66). Students have a positive attitude towards sustainability, but their willingness to perform sustainability behaviours in related projects or activities does not show the same direction. The implication is that this study can contribute to the Technical and Vocational Training Education Division (BPLTV) as a guide in the transformation towards a formal sustainable curriculum in the Fashion Design program at vocational colleges.